Existence results for generalized variational inequalities via topological methods - Benedetti, Irene; Mugelli, Francesco; Zecca, Pietro (Topological Methods in Nonlinear Analysis, 2012)
In this paper we find existence results for elliptic and parabolic nonlinear variational inequalities involving a multivalued map. Both cases of a lower semicontinuous multivalued map and an upper semicontinuous one are considered.